2022
DOI: 10.1186/s13052-022-01319-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic subtypes and phenotypic characteristics of 110 patients with Prader-Willi syndrome

Abstract: Background Prader-Willi syndrome (PWS) is a complex disorder caused by impaired paternally expressed genes on chromosome 15q11-q13. Variable findings have been reported about the phenotypic differences among PWS genetic subtypes. Methods A total of 110 PWS patients were diagnosed from 8,572 pediatric patients included from July 2013 to December 2021 by MLPA and MS-MLPA assays. Atypical deletions were defined by genomic CNV-sequencing. Maternal unip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…This lack of difference in cognitive profiles may be due to higher heterogeneity inside each group. In subjects with disomy, cognitive function seems more preserved in the case of uniparental disomy, heterodisomy being more favorable than isodisomy (Zhang et al, 2022). In subjects with deletion, phenotype varies according to the length of the deletion.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of difference in cognitive profiles may be due to higher heterogeneity inside each group. In subjects with disomy, cognitive function seems more preserved in the case of uniparental disomy, heterodisomy being more favorable than isodisomy (Zhang et al, 2022). In subjects with deletion, phenotype varies according to the length of the deletion.…”
Section: Discussionmentioning
confidence: 99%
“…8 Specifically, hypopigmentation, which is a symptom of suspected PWS, was observed less frequently in the UPD group than in the deletion group. 40,41 In our report, we were unable to evaluate the rates of hypopigmentation because of a lack of data on dysmorphic features. In addition, commercial unavailability of methylation testing in Japan until 2018, and use of fluorescence in situ hybridization as the first choice for detection of deletion at many facilities, may also be related to the delayed diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…The reason for later diagnosis of patients with UPD compared to those with deletions was the less typical clinical phenotype 8 . Specifically, hypopigmentation, which is a symptom of suspected PWS, was observed less frequently in the UPD group than in the deletion group 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…51 There are two types of UPD, isoUPD and heteroUPD, which may play a part in the genotype variation, especially for anxiety. 12 However, we did not analyze difference between the subtypes of UPD and phenotypes. Further studies on the phenotypes among different subgenotypes of deletion and UPD are required.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] On the other hand, UPD patients are less likely to have typical facial features, skin picking, or hypopigmentation. 1,12 However, results from different studies are not consistent. Dobrescu et al 13 found no differences between the deletion and UPD types in specific facial features, hypopigmentation, sleep disorder, obesity, and scoliosis, though they only had a total of 35 individuals with PWS in that study.…”
Section: Introductionmentioning
confidence: 99%